Determinants of audit delay: an analysis of post Malaysian Financial Reporting Standards (MFRS) adoption / Najihah Marha Yaacob and Norazamina Mohamed - Yaacob, Najihah Marha; Mohamed, Norazamina (UiTM Press, 2021)
Changes in standards will need more audit effort and, as a result, audit delays are anticipated to rise. This study intended to determine the factors that influence Malaysian audit timeliness in the years after complete implementation of the Malaysian Financial Reporting Standards (MFRS). This study used 534 firm-year observations of non-financial firms listed on Bursa Malaysia's main market and the ACE market. The causes of audit delays were determined using panel data analysis from 2017 to 2018. Panel regression results revealed that four variables have significant relationships with audit delays, which include firm size, firm risk, firm complexity, and international audit firm. While the accounting period year-end and type of industry of the company implied no relationship with audit delays, the findings provide evidence that the main determinants of audit delays, namely the client's size, complexity and risk endure across the era and realm. Moreover, this study provides support for the brand name theory that signifies a positive relationship between reputation, price, and quality. The results provide tangible effects of audit delays in companies during post-MFRS adoption, and these findings should provide useful insight into the accounting profession and the corporate sector as a whole.